2018
DOI: 10.1111/jvim.15326
|View full text |Cite
|
Sign up to set email alerts
|

Plasma cytokeratin‐18 concentrations as noninvasive biomarker of early gastrointestinal toxicosis in dogs receiving toceranib

Abstract: BackgroundNo biomarkers for the early detection of gastrointestinal (GI) toxicosis secondary to antineoplastic treatment are recognized in veterinary medicine. Toceranib causes GI toxicosis in dogs.Hypothesis/ObjectiveTo assess if changes in plasma cytokeratin 18 (CK18) concentration, measured in dogs being treated with toceranib phosphate, can predict the onset of GI toxicosis. We hypothesize that an increase in CK18 concentrations will be detected before the development of GI toxicosis in dogs treated with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Alternatively, our lack of significant changes in CK18 levels may be due to poor intrinsic sensitivity of CK18 as a biomarker for apoptosis of the intestinal epithelial cells secondary to cytotoxic chemotherapy drug administration in dogs. Research on CK18 as a biomarker for GI disease is limited to a small number of human and veterinary studies; therefore, more sensitive and accurate biomarkers in the setting of chemotherapy‐induced GI toxicosis may exist that warrant investigation (Greystoke et al., 2011; Jugan et al., 2018; Kovac et al., 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, our lack of significant changes in CK18 levels may be due to poor intrinsic sensitivity of CK18 as a biomarker for apoptosis of the intestinal epithelial cells secondary to cytotoxic chemotherapy drug administration in dogs. Research on CK18 as a biomarker for GI disease is limited to a small number of human and veterinary studies; therefore, more sensitive and accurate biomarkers in the setting of chemotherapy‐induced GI toxicosis may exist that warrant investigation (Greystoke et al., 2011; Jugan et al., 2018; Kovac et al., 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Studies aimed at identifying biomarkers of epithelial toxicosis following doxorubicin administration in humans found that serum CK18 concentrations increased significantly in patients that experienced high grade GI toxicosis (Gibb et al., 2013; Greystoke et al., 2011). In veterinary patients, CK18 has been evaluated as a systemic marker of epithelial damage in healthy dogs following antimicrobial administration and in dogs with mast cell tumours treated with toceranib phosphate, a tyrosine kinase inhibitor (Jugan et al., 2018; Kovac et al., 2018). While alterations in plasma CK18 levels in healthy dogs receiving antimicrobial drugs were observed and suggest an effect on gastrointestinal epithelium, CK18 levels did not correlate with the severity of GI toxicosis in dogs treated with toceranib.…”
Section: Introductionmentioning
confidence: 99%